Influence of porosity on fatigue behaviour of 18Ni300 steel SLM CT specimens at various angles - Moreno Cerezo, Pablo; Aguilera-García, José Antonio; García-González, Antonio Luis; López-Crespo, Pablo (MDPI, 2024)
in order to improve understanding of the fatigue behaviour in additive manufactured samples, this research delves into the challenging interplay between building parameters, particularly fabrication angles, and the presence of pores. The primary objective is to explore the characterisation of these pores and unravel their relationship with the fatigue properties of the material under investigation. Through a systematic analysis of porosity distribution in various fabrication orientations, supplemented by a detailed examination of the elemental dispersion around specific porous structures using energy-dispersive X-ray spectroscopy, a consistent behavioural pattern emerges across the samples. In assessing fatigue behaviour, an examination of the variables reveals that only area and aspect ratio significantly influence the behaviour of the samples. Such studies can contribute substantially to academic research in the field of material science and engineering.
Keywords: Fatiga; Porosidad; 18Ni300; Additive manufacturing (AM); Porosity; Selective laser melting (SLM); Microstructure; Fatigue